The situation of nursing education in Latin America and the Caribbean towards universal health - Silvia Helena De Bortoli Cassiani; Lynda Law Wilson; Sabrina de Souza Elias Mikael; Laura Morán Peña; Rosa Amarilis Zarate Grajales; Linda L. McCreary; Lisa Theus; Maria del Carmen Gutierrez Agudelo; Adriana da Silva Felix; Jacqueline Molina de Uriza; Nathaly Rozo Gutierrez (Revista Latino-Americana de Enfermagem)
Objective: to assess the situation of nursing education and to analyze the extent to which baccalaureate level nursing education programs in Latin America and the Caribbean are preparing graduates to contribute to the achievement of Universal Health. Method: quantitative, descriptive/exploratory, cross-sectional study carried out in 25 countries. Results: a total of 246 nursing schools participated in the study. Faculty with doctoral level degrees totaled 31.3%, without Brazil this is reduced to 8.3%. The ratio of clinical experiences in primary health care services to hospital-based services was 0.63, indicating that students receive more clinical experiences in hospital settings. The results suggested a need for improvement in internet access; information technology; accessibility for the disabled; program, faculty and student evaluation; and teaching/learning methods. Conclusion: there is heterogeneity in nursing education in Latin America and the Caribbean. The nursing curricula generally includes the principles and values of Universal Health and primary health care, as well as those principles underpinning transformative education modalities such as critical and complex thinking development, problem-solving, evidence-based clinical decision-making, and lifelong learning. However, there is a need to promote a paradigm shift in nursing education to include more training in primary health care.